The Extent of Measurement Error in Longitudinal Earnings Data: Do Two Wrongs Make a Right? - Bound, John; Krueger, Alan B. (Journal of Labor Economics, 1991)
This article examines the properties and prevalence of measurement error in longitudinal earnings data. The analysis compares matched Current Population Survey data to administrative Social Security payroll tax records. In contrast to typically assumed properties of measurement error, the results indicate that errors are serially correlated over two years and negatively correlated with true earnings (i.e., mean reverting). In a cross section, the ratio of the variance of the signal to the total variance is 0.82 for men and 0.92 for women. These ratios fall to 0.65 and 0.81 when the data are specified in first differences. Longitudinal earnings data may be more reliable than previously believed. Copyright 1991 by University of Chicago Press.